Dunn, Ed., Something That Will Surprise The World - The Essential Writings Of The Founding Fathers - Riggs, Dawn (Teaching History: A Journal of Methods, 2008)
Every teacher who makes a commitment to using primary sources in the classroom either faces a lack of easily accessible materials or such a cornucopia of resources that making the best selection is time-consuming and complicated. For those educators who teach early American history or history of the American Revolution, the latter scenario is more often the case. The founders were prolific writers and the ongoing publication of their public and personal writings shows no sign of tapering off in the years to come.